Combined Recirculatory-compartmental Population Pharmacokinetic Modeling of Arterial and Venous Plasma S(+) and R(–) Ketamine Concentrations. (August 2018) - Henthorn, Thomas K.; Avram, Michael J.; Dahan, Albert; Gustafsson, Lars L.; Persson, Jan; Krejcie, Tom C.; Olofsen, Erik
Abstract : What We Already Know about This Topic: Recirculatory pharmacokinetic models describe intravascular mixing by incorporating cardiac output and its distribution to characterize the oscillations of arterial and venous drug concentrations in the minutes after rapid IV drug administration Arterial drug concentrations during a drug infusion are higher than venous concentrations but are lower than postinfusion venous concentrations What This Article Tells Us That Is New: A ketamine dataset with simultaneously collected arterial and venous blood samples was used to develop an intravascular mixing model that reconciled the divergent arterial and venous concentration versus time relationships during and after drug infusion Higher arterial concentrations during drug infusion result from the contribution of both partially mixed drug from the upstream infusion and mixed recirculating drug The partially mixed concentration is proportional to the ratio of the drug infusion rate and cardiac output Higher postinfusion venous concentrations are due to contributions of drug eluting from tissue Background: The pharmacokinetics of infused drugs have been modeled without regard for recirculatory or mixing kinetics. We used a unique ketamine dataset with simultaneous arterial and venous blood sampling, during and after separate S(+) and R(–) ketamine infusions, to develop a simplified recirculatory model of arterial and venous plasma drug concentrations. Methods: S(+) or R(–) ketamine was infused over 30 min on two occasions to 10 healthy male volunteers. Frequent, simultaneous arterial and forearm venous blood samples were obtained for up to 11 h. A multicompartmental pharmacokinetic model with front-end arterial mixing and venous blood components was developed using nonlinear mixed effects analyses. Results: A three-compartment base pharmacokinetic model with additional arterial mixing and arm venous compartments and with shared S(+)/R(–) distribution kinetics proved superior to standard compartmental modeling approaches. Total pharmacokinetic flow was estimated to be 7.59 ± 0.36 l/min (mean ± standard error of the estimate), and S(+) and R(–) elimination clearances were 1.23 ± 0.04 and 1.06 ± 0.03 l/min, respectively. The arm-tissue link rate constant was 0.18 ± 0.01 min –1, and the fraction of arm blood flow estimated to exchange with arm tissue was 0.04 ± 0.01. Conclusions: Arterial drug concentrations measured during drug infusion have two kinetically distinct components: partially or lung-mixed drug and fully mixed-recirculated drug. Front-end kinetics suggest the partially mixed concentration is proportional to the ratio of infusion rate and total pharmacokinetic flow. This simplified modeling approach could lead to more generalizable models for target-controlled infusions and improved methods for analyzing pharmacokinetic-pharmacodynamic data. Abstract : A ketamine dataset with simultaneously collected arterial and venous blood samples was used to develop an intravascular mixing model that reconciled the divergent arterial and venous concentration versus time relationships during and after drug infusion. Higher arterial concentrations during drug infusion result from the contribution of both partially mixed drug from the upstream infusion and mixed recirculating drug. The partially mixed concentration is proportional to the ratio of the drug infusion rate and cardiac output. Higher postinfusion venous concentrations are due to contributions of drug eluting from tissue.Supplemental Digital Content is available in the text.